Pemekaran Wilayah dan Otonomi Daerah Pasca Reformasi di Indonesia: Konsep, Fakta Empiris dan Rekomendasi ke Depan - Andik Wahyun Muqoyyidin (Jurnal Konstitusi, 2013)
Basically, the regional expansion is a form of regional autonomy and is one of the things that need to be considered because of the presence of regional expansion is expected to further maximize equitable regional development and regional development. In the spirit of regional autonomy was also the emerging paradigm of regional expansion to speed up the implementation of development, ease of public service to the community, as well as the acceleration of social welfare. In the reform era, the space for the area for the proposed establishment of a New Autonomous Region opened wide by the regional expansion policy based on Law no. 22, 1999. With such a policy, the policy of regional expansion is now more dominated by the political process rather than technocratic  process.